Texts, Transmissions, Receptions Modern Approaches to Narratives - Lardinois, André; Levie, Sophie; Hoeken, Hans; Lüthy, Christoph (Radboud Studies in Humanities, 2014)
The papers collected in this volume study the function and meaning of various kinds of narrative texts from the perspective of New Philology, Linguistics, Iconography and Reception studies. Their purpose is to understand the workings of narrative texts. Readership: All interested in the workings of narrative texts and especially those who approach narrative texts from the perspective of iconography, linguistics, new philology or reception studies.